Resources and planning for economic development - "Bhargava , Archana" (New Delhi, 1991)
The inter-relationship between man, resources and development is the point of discussion and elaboration in the present volume. In the wake of integrated rural regional development, it is imperative to envisage development as socio-economic change for betterment of masses involving local resources and incorporate interest. Such a structural change in orientation of planning requires resource evaluation and allocation on microscale in detail. Utilizing the contemporary techniques, evaluation of potentials, present utilization and possibilities of optimum utilization of resources of a relatively less developed region, i.e., Sagar Division of Madhya Pradesh is attempted. This division provides an example of how only basic attributes of resources are taken care of ignoring the combinational ones in the existing system of spatial organisation developed under top-down planning. The widening disparity can be minimized by planning on micro-level. A comparatively new approach of identification of planning units, incorporating characteristics of both formal and functional regions, has been attempted. As such the present volume can serve as model for resource-based development planning of depressed regions.
Keywords: Economic Development